Enhancing adaptation to climate variability in the East African highlands: a case for fostering collective action among smallholder farmers in Kenya and Uganda. (2nd January 2018) - Ombogoh, Douglas Bwire; Tanui, Joseph; McMullin, Stepha; Muriuki, John; Mowo, Jeremias
Abstract : There is an increasing recognition of the role of climate change adaptation among smallholder farmers in rain-fed agriculture in Africa. Collective action among smallholder farmers has been suggested as influencing local adaptation processes hence the need to evaluate its impact in different contexts. This paper provides evidence of collective action in enhancing local adaptation to climate variability. It determines the importance of different forms of collective action for enhancing adaptation. Through simple random sampling, a survey of 240 households in Embu County in Kenya and 200 households from Kapchorwa district of Uganda was undertaken. Focus-group discussions involving farmer groups and local government representatives were performed to triangulate information collected through the surveys. The results show a positive relationship between membership in farmer groups and adaptation to climate variability in both sites. Four main components of collective action were identified in Embu and these included the development of internal group capacities, assets mobilization and management, collective marketing, and management of human and natural capital. In Kapchorwa, the development of internal group capacities, risk spreading, and financial resources were significant. We argue that local-level governance and institutional arrangements for collective action are critical for successful adaptation to climate variability.